Quality of life of mothers who have children with developmental disabilities (Journal of Health Sciences, 2020)
Introduction: The primary source of strength and support is the child’s family. A special role in caring for a child with developmental disabilities is played by his mother. The objective of this research is to find out the assessment of the quality of life (QOL) of disabled children mothers as well as to research the relation of sociodemographic variables of the respondents, as specified in this study and estimate the quality of their life and health.Methods: The cross-sectional study was performed by the use of the descriptive-analytical method. In a targeted association of families which have children and persons with difficulties was conducted this research on a sample of 100 registered mothers. The research instrument was the standardized questionnaire for QOL, the World Health Organization QOL-BREF and the users’ records of the mothers in the association.Results: The average age of the respondents was M = 48. 01 ± 11. 68. About 62% of the respondents are married, 54% have a high school diploma, 67% are not employed, 68% of the respondents did not declare to have health problems, and among those who declared to have health problems, the most common disease was diabetes mellitus. The average number of household members was M = 3. 44 members. The number of the household members was significantly and positively related to the domain of social interaction (rs = 0. 219; p < 0. 05), the domain of the environment (rs = 0. 220; p < 0. 05) and to the general QOL (rs = 0. 227; p < 0. 05). The age of the respondents was significantly and positivelyrelated only to the environmental domain (rs = 0. 205; p < 0. 05). The respondents who drive a car showed a significantly higher level of QOL in the field of mental health (p = 0. 042) and the environment (p = 0. 005). Concerning mothers with higher incomes rate, their QOL was better in the following domains: Physical health (p = 0. 030), mental health (p = 0. 002), environment (p = 0. 000001), and general QOL (p = 0. 0002).Conclusion: The respondents with a larger number of household members, those who have the support of family members, who were without health problems, and who independently use own car for transportation, consider their QOL as being better. Therefore, a promotional – preventive program for improving the life quality of mothers of children and persons with disabilities should include accessible life in the community and the ability to recognize the unique needs of the entire family of children and persons with disabilities.